A regionális együttműködés feltételei Közép- és Kelet-Európában - Illés, Iván (Tér és Társadalom, 1997)
The study is focused on the forms and types of regional collaboration that effects the economic and social development of the nations of Europe increasingly. The importance of regionalism is rising in parallel with the process of globalisation: the former is a device of saving local autonomy and democracy. It has significant role in Central and Eastern Europe where the nations are linked by their borders, traditional economic relations and separated by political conflicts. There are several factors hindering the development of co-operation that is rather scarce and embryonic, such as the lower level of decentralisation and lack of an overall integration process in Eastern Europe, furthermore, the scarcity of fmancial resources available for promoting programs of this kind. In the second part of the study, the author analysed some examples of two types of regional co-operation, macro-regional collaboration projects and cross-border regional development programs. The former ones are multi-lateral projects initiated by regions of EU-member and non-member countries. The success of these programs is varying and heavily dependent on the available financial resources (Carpathian Region) and the compatibility of decision-making levels (Association Alps-Adria). Hungary is involved in the CADSES program that is part of the INTERREG II initiated by the European Union. The author detailed the weak points and the possible ways of exploitation of the program. The INTERREG II and PHARE CBC programs were established to promote cross-border co-operation along the eastern boundary of the EU. German-Polish and German-Czech Euroregions were formed in this framework. The experiences of the participants such as differences of the institutional background, decision-making and fmancial systems that may retard the development of the economic relations could be utilised by Hungarian regions.